ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2011-2015) - Jessica Stephanie; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2017)
The aim of this study is to find determinant factors of auditor switching among manufacturing companies. Variables that considered to affect are management changing, qualified opinion, company size, audit quality, financial distress and audit fees. The populations in this study are all manufacturing companies that listed in Indonesia Stock Exchange, period 2011-2015. The methods used to determine sample is purposive sampling with 125 samples are obtained. The analysis showed that there is negative and significant effect of client size to auditor switching, while change in management, audit quality, financial distress, qualified opinion and audit fee are not.